FIGURES OF SPEECH AS MEANS OF IMAGE «THE SUN» CONCEPTUALIZATION IN VASYL STUS’ POETRY - RIZNYK, Yuliia (Linguistic and Conceptual Worldviews, 2022)
The article examines the peculiarities of the use of tropes as a means of linguistic objectification of the image «the sun» in Vasyl Stus’ poetry. It is defined that an ethnostereotype is a form stable mental structures that are enshrined in language and accumulate condensed knowledge of the people about the world, themselves and others, that is created due to the interaction of language, culture and consciousness and have axiological and epistemological functions. Figures of speech as signs of language, thinking and culture reflect the characteristics of the writer’s ethnopsychological identity and are an important tool for modeling the ethnic picture of the world. As a result of correlation of the associative-image system with cultural-national stereotypes, ideas and standards, figures of speech acquire cultural-marked connotations. The analisys of the linguistic explication of Vasyl Stus’s individual-authorial picture of the world shows that one of the productive ethnic constants is the ethnostereotype the sun. The sun in Vasyl Stus’ poetry is objectified in metaphors, which reveal the following ethnocultural meanings: a symbol of pagan and Christian God, the All-Seeing Deity and the power of God, which is also realized in the context of God’s judgment; the supreme truth; the source of light, heat and life; the beginning of the world; a pleasant person; inspiration, kindness, greatness. Following the folklore tradition, the writer associates the absence of the sun with death and the decline of nature, old age, the end of a certain period of life. Epithets that characterise the ethnostereotype describe it depending on the time of day (morning, noon, night), seasons (summer, spring), distance from the Earth (high), reflecting the idea of the impact of this light on the life of nature and the mental state of people. The color epithets of the sun (fiery, spring, purple) objectify the belief in the prediction of the weather and the future, depending on the type of light. Oxymoron epithets (midnight, night, cold, black) should be singled out, indicating the significant psychological influence of the sun on a person. The sun as the center of the Ukrainian macro-space is verbalized by the epithets Trypillia, cherry, the sun of Ukraine.